Recovering Civility during COVID-19 - Bonotti, Matteo (Springer Nature, 2021)
This Open Access book examines many of the challenges posed by the COVID-19 pandemic through the distinctive lens of civility. The idea of civility appears often in both public and academic debates, and a polarized political climate frequently leads to allegations of uncivil speech and behaviour. Norms of civility are always contested, even more so in moments of crisis such as a global pandemic. A focus on civility provides crucial insight and guidance on how to navigate the social and political challenges resulting from COVID-19. Furthermore, it offers a framework through which citizens and policymakers can better understand the causes and consequences of incivility, and devise ways to recover civility in our social and political lives.